Interactive Education to Improve Traffic Safety Awareness at SMAN 1 Harau Through Card Games - Fithriyah Patriotika; Rizky Indra Utama; Faisal Ashar (CIVED, 2025)
Traffic safety remains a significant issue among adolescents in Indonesia. Senior high school students represent a particularly susceptible demographic. This community service initiative aimed to enhance students' understanding of road safety at SMAN 1 Harau via an interactive card game called Road Smart Card. The program was executed with a one-group pretest-posttest design involving 30 students. The Traffic Smart Card featured depictions of traffic signs, authentic traffic scenarios, and educational inquiries to promote dialogue and contemplation. The results indicated a notable enhancement in students' knowledge, with a posttest mean score of 90.50 compared to a pretest mean score of 71.17, reflecting a 27.17% gain. The mean N-Gain score is 0.68, categorizing it as high and affirming the efficacy of the learning medium. Fifty percent of students achieved a high gain classification, while the remaining fifty percent fell into a medium group, with no students categorized as low. Over 90% of the students actively participated in group discussions and game activities, fostering an engaging and enjoyable learning environment. The therapy also resulted in emotional and behavioral changes in addition to cognitive improvements. The school committed to including media in standard educational practices, the School Safety Patrol extracurricular program, and OSIS activities. The program effectively enhanced understanding and road safety culture among young students in a pertinent and sustainable manner.